Strategic Supply Chain Structure Design for a Proprietary Component Manufacturer - Xu, Yi; Gurnani, Haresh; Desiraju, Ramarao (Production and Operations Management, 2010)
This paper examines the choice of supply chain structure for a proprietary component manufacturer (PCM). The PCM, who is the sole supply source of a critical component used to assemble an end product, can either provide its component to an original equipment manufacturer (OEM) in the end‐product market (component supplier structure), develop the end product exclusively under its own brand (monopoly structure), or provide the component to the OEM as well as develop the end product under its own brand (dual distributor structure). Typically, the end products of the PCM and the OEM will be differentiated, and the OEM tends to have a capability advantage (compared with the PCM) in producing the end product. Our paper studies the impact of this degree of differentiation and capability advantage on the optimal choice of distribution structure. We then investigate how investing in component branding, enhancing the value of the end product, using alternative supply contracts, and product valuation uncertainty influence the PCM's optimal choice of distribution structure.